Utilization of wall magazines in improving fifth-grade students' writing skills - Natasya Navira Elberni; Febrina Dafit (Inovasi Kurikulum, 2024)
Writing skills are something that students cannot ignore. Therefore, using wall magazine media can significantly improve students' writing skills in elementary schools. This research aims to determine the plan, implementation, and evaluation of the use of wall magazines in improving the writing skills of VA students at SDN 19 Mandau, Bengkalis Regency. This research uses qualitative methods with the type of classroom action research (PTK). The research subjects in this study were 26 VA class students at SDN 19 Mandau. Data collection techniques in this research used observation and tests. Meanwhile, the instruments used are observation sheets and test sheets. The data analysis technique in this research was carried out using qualitative descriptive analysis. Based on the research results, it can be seen that the use of wall magazines can improve the writing skills of class VA students at SDN 19 Mandau. Student learning outcomes using wall magazines increased, where in cycle I, the average obtained was 74 with sufficient classical completeness. In contrast, in cycle II, there was an increase with an average of 80 and very good classical completeness.   Abstrak Keterampilan menulis merupakan hal yang tidak bisa diabaikan bagi peserta didik. Oleh karena itu, pemanfaatan media majalah dinding dapat signifikan dalam meningkatkan kemampuan menulis peserta didik di sekolah dasar. Tujuan penelitian ini adalah untuk mengetahui rencana, pelaksanaan serta evaluasi penggunaan majalah dinding dalam meningkatkan kemampuan menulis peserta didik VA di SDN 19 Mandau Kabupaten Bengkalis. Pendekatan dalam penelitian ini menggunakan metode kualitatif dengan jenis penelitian tindakan kelas (PTK). Subjek penelitian pada penelitian ini adalah peserta didik kelas VA di SDN 19 Mandau berjumlah 26 peserta didik. Teknik pengumpulan data pada penelitian ini menggunakan observasi dan tes. Sedangkan instrumen yang digunakan adalah lembar observasi dan lembar tes. Teknik analisis data pada penelitian ini dilakukan dengan analisis deskriptif kualitatif. Berdasarkan hasil penelitian, dapat diketahui bahwa penggunaan majalah dinding dapat meningkatkan kemampuan menulis peserta didik kelas VA di SDN 19 Mandau. Hasil belajar peserta didik dengan menggunakan majalah dinding mengalami peningkatan dimana pada siklus I rata-rata yang didapatkan yaitu 74 dengan ketuntasan klasikal cukup, sedangkan pada siklus II mengalami peningkatan dengan rata-rata 80 dan ketuntasan klasikal sangat baik. Kata Kunci: kemampuan menulis; majalah dinding; sekolah dasar